1987
DOI: 10.1093/clinchem/33.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Simple spectrophotometric determination of urinary albumin by dye-binding with use of bromphenol blue.

Abstract: This procedure for routine quantification of albumin in urine is based on the dye-binding properties of albumin with bromphenol blue. The absorbance of 100 microL of urine mixed with 3 mL of color reagent is measured against blank reagent at 610 nm after 30 s. Results vary linearly with albumin concentration up to 6 g/L. The reaction is pH independent in the physiological range. It is not subject to substantial interference by uric acid, creatinine, calcium, sodium chloride, or bilirubin. The presence of globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The method has been found to have a good precision as is evident from low coefficients of variation. In comparison to the precision study reported [5] this method shows more precision (Table 2) at the lower concentration of albumin employing 1:5 ratio of urine(sam-pIe) and reagent. The mean values observed in normals are higher than reported (6)(7)(8) though within the suggested normal range.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The method has been found to have a good precision as is evident from low coefficients of variation. In comparison to the precision study reported [5] this method shows more precision (Table 2) at the lower concentration of albumin employing 1:5 ratio of urine(sam-pIe) and reagent. The mean values observed in normals are higher than reported (6)(7)(8) though within the suggested normal range.…”
Section: Discussionmentioning
confidence: 57%
“…The mean values observed in normals are higher than reported (6)(7)(8) though within the suggested normal range. This could be due to some positive bias be› cause of various non-protein constituents of urine, or globulins if present [5). This needs further study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bromophenol blue has been used extensively to quantify the amount of protein or peptide in a solution. , A test method to visualize surface peptide using bromophenol blue was adapted from these solution test methods and was employed as previously noted . Approximately 4.5% of Chr-1 and 1% of Chr-3 was present at the coating surface.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical Assays: The cells were lysed in a lysis buffer containing 50 mM Tris-HCl (pH 7.5), 150 mM NaCl, 0.1% SDS, 1% TritonX-100, and 1% sodium deoxycholate with sonication (20 kHz, 10 s, twice) in an ultrasonic homogenizer (UH-50, Tokyo, Japan). Lipid peroxidation products were measured using thiobarbituric acid reactive substances (TBARS reaction) and total thiols were monitored by Schosinsky assay [13]. Spectrophotometric assays were performed with the AnalyticYena spectrophotometer and the winASPECT software (Yena, Germany).…”
Section: Methodsmentioning
confidence: 99%